CONSTITUTIONALITY OF THE DISMISSAL OF THE FIRST COMMUNIST MINISTRY IN KERALA - Ajayan.T (GLOBAL JOURNAL OF MULTIDISCIPLINARY STUDIES, 2015)
In the first general election held to the Kerala State Legislative Assembly in February- March 1957, the Communists won sixty seats out of 126. With the support of five independents, the Communists formed government under the leadership of E.M.S. Namboodiripad on 5 April 1957. But the ministry was short lived. It was dismissed on 31 July 1959 by the President of India under Article 356 of the Constitution of India. There is no unanimity on the constitutionality of the dismissal of the first Communist ministry in Kerala and it has been differed according to the political views of the authors. Nor has the previous studies analysed the options available to the Union Government other than the dismissal of the ministry. The present paper fills this gap through the examination of the Constituent Assembly Debates and the intention of the framers of the constitution behind the inclusion of the articles empowering the Union of India to intervene in States.